Afinidades eletivas: ética religiosa e utopias sociais - análise psicossocial de uma organização de base comunitária - Wrasse, Dílson (2012)
This dissertation has the purpose of analysing the process of definition of the awareness and identity of a political subject historically involved between the religious ethics and social utopic conceptions of reality transformation and human emancipation. We used as methodological strategic data collection and analysis the organizational-historical study case favoring the analysis of documents elaborated throughout history. More relevance was given to the study case the Ação Comunitária Paroquial Jardim Colonial, that gathers 10 service units for children and youth and that is inserted in the context of the outskirts of São Paulo, Zona Leste region, District of Iguatemi. The political subject under analysis came out of the Clube das Mães movement (Mother s Club movement) in the 70 s, and gained strength through the Ecclesial Base Communities (CEBs) , became institutional as Political Formation Center (Centro de Formação Política), consolidated itself as a social work related to the Movement for Children and Youth Rights (Movimento de Defesa dos Direitos da Criança e do Adolescente), currently incorporated to state policies having as main partner Secretaria de Assistência Social do Município de São Paulo (Social Assistance Secretary of the Municipality of São Paulo).It is evident that many community based organizations that appeared in the city of São Paulo motivated by the action of the Igreja Popular (People Church) engaged in social work, but do not have mediators, as in the past, in the formation and definition of the identity of the political subject. The reduction of internal and external political spaces allows group processes to build their identities so that they can, in turn, redefine their positions in society